Investigating the impact of hybrid asphalt mixtures on the mechanical properties - Wan Noor Hin, Mior Sani; Putra Jaya, Ramadhansyah; Khairil Azman, Masri (IOP Publishing Ltd., 2025)
This study explores the mechanical performance of hybrid asphalt mixtures incorporating palm oil fuel ash (POFA), garnet waste, and sawdust as sustainable materials for asphalt modification. The aim is to assess the impact of these materials on key mechanical properties, including creep modulus and indirect tensile strength (ITS). A series of asphalt mixtures with varying hybrid content (0%, 3%, 6%, and 9%) by weight of conventional asphalt of 60/70 PEN grade were prepared using wet blending process and evaluated. Among the mixtures tested, the 6% hybrid asphalt mixture exhibited optimal mechanical performance, with a creep modulus of 32.7 MPa and an indirect tensile strength of 1492 kPa. Statistical analysis through one-way ANOVA confirmed a significant effect of hybrid content on creep stiffness modulus (F = 121.44, p < 0.001), underscoring the critical role of hybrid content in enhancing the stiffness of asphalt mixtures. These results indicate that the inclusion of POFA, garnet waste, and sawdust at 6% significantly enhances the stiffness and tensile resistance of the asphalt, making it a viable option for improving the durability and sustainability of pavements. The findings underscore the potential of hybrid materials in advancing the development of eco-friendly asphalt mixtures with superior mechanical properties.